Ulema and Tolerance Fiqh: A Critical Examination of the 2024 MUI Fatwa Commission’s Ijtima’ on the Inter-Religious Relations - Kurniawan, Edi; Yahya Shaykh Ahmad; Muhammad Romli Samae, Syarif Bin (Al-Wasatiyah: Journal of Religious Moderation, 2025)
This article examines the construction of tolerance fiqh in the 2024 Resolution of the Ijtima' Nasional VIII of the Fatwa Commission of the Indonesian Ulema Council (MUI), which includes perspectives on interreligious relations, greetings across faiths, and tolerance in the context of religious festivities. The issuance of these guidelines is closely tied to Indonesia's religious diversity, requiring clear normative guidance and boundaries rooted in Islamic law to promote harmonious interfaith interaction. Therefore, this article looks at the ideas and boundaries of tolerance found in the guidelines by using the principles of maqāṣid al-sharīʻah (the higher goals of Islamic law) and fiqh al-aqalliyyāt (Islamic laws for minorities). It further explores the legal reasoning, normative structure, and socio-religious implications within Indonesia's pluralistic society. This literature-based study uses the 2024 resolution as the primary source, supported by secondary materials, including journals and classical works in fiqh and uṣūl al-fiqh. This article concludes that the guidelines for tolerance in Islamic law clearly separate beliefs, worship, and social interactions. This distinction allows for mutual respect and interfaith tolerance while upholding boundaries, such as prohibiting interreligious greetings, using religious symbols from other faiths, and participating in non-Muslim religious celebrations. The resolution thus maintains a firm commitment to ḥifẓ al-dīn (protection of religion) while providing measured flexibility in social engagement. This article contributes to developing a contextual and balanced Islamic legal methodology for managing religious diversity in Indonesia.